Accuracy Degradation Model and Residual Accuracy Life Prediction of CNC Machine Tools Based on Wiener Process. Issue 3 (January 2021) - Li, Shilin; Ran, Yan; Zhang, Genbao; Zhang, Dingfei
Abstract: In order to predict the accuracy residual life of CNC machine tools, an accuracy degradation model and accuracy residual life prediction method of CNC machine tools based on accuracy degradation data are proposed. Considering the non-linear and uncertainties in the process of accuracy degradation, an accuracy degradation model of CNC machine tools was established based on the nonlinear Wiener process; The accuracy failure is judged when the measured accuracy value exceeds the failure threshold for the first time. An accuracy residual life prediction model based on Inverse Gaussian distribution is established, and the accuracy residual life is calculated as a probability density function. To solve the problem of lack of historical data and prior information for a single CNC machine tool, particle filter is used to recursively update the posterior values of the model parameters based on the current observation data to achieve continuous optimization of the residual life prediction results; Finally, the correctness and effectiveness of the accuracy degradation model and the prediction method of the accuracy residual life are verified through the example analysis of the accuracy degradation experimental data of CNC machine tool.